2010
DOI: 10.4103/1319-3767.58762
|View full text |Cite
|
Sign up to set email alerts
|

Short-duration furazolidone therapy in combination with amoxicillin, bismuth subcitrate, and omeprazole for eradication of Helicobacter pylori

Abstract: Background/Aim:Resistance to metronidazole is one of the most common reasons for Helicobacter pylori treatment failure with the classic triple therapy. The clarithromycin-based regimen is not cost-effective for use in developing countries. Though furazolidone is a great substitute it has many side effects. Decreasing the duration of treatment with furazolidone to 1 week may help decrease the drug's side effects.Aim:To study the efficacy and side effects of furazolidone when given for 1 week in combination with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 22 publications
0
7
0
Order By: Relevance
“…achieved relatively poor results with PP ranging from 56% to 85.7% (weighted mean for PP and ITT were 71% and 67%, respectively, Table 1). There were 4 studies [32;37;41;42] using a sequential therapy with furazolidone 200 mg b.i.d. given for the first week of a two week therapy.…”
Section: Resultsmentioning
confidence: 99%
“…achieved relatively poor results with PP ranging from 56% to 85.7% (weighted mean for PP and ITT were 71% and 67%, respectively, Table 1). There were 4 studies [32;37;41;42] using a sequential therapy with furazolidone 200 mg b.i.d. given for the first week of a two week therapy.…”
Section: Resultsmentioning
confidence: 99%
“…[18,19] The major limitation for widespread use of FZD appears because of its side effects related to digestive tract, such as nausea, anorexia, dizziness, abdomen discomfort etc., which are due to monoamine oxidase inhibitory effects of this drug. [20] Additionally, doses and duration of FZD also affect the incidence of side effects. [16] A study compare the incidence of adverse reactions with 14-day regimens containing FZD has found that as the dose increases from 100 to 200 mg (twice a day), the severe or intolerant side effects leading to the discontinuation of treatment increased from 6% to 20%, including dizziness, abdominal pain, and anorexia.…”
Section: Discussionmentioning
confidence: 99%
“…Many researchers have reported high levels of resistance to metronidazole (37%) and clarithromycin (28%) (2,3,(7)(8)(9)(10)(11). Fakheri et al (12), in a study, showed that furazolidone-based quadruple therapy is a good alternative for eradication of H. pylori infection in regions with high resistance to metronidazole and clarithromycin.…”
Section: Introductionmentioning
confidence: 99%
“…Given the high pill burden, the increased frequency of administration, and the prolonged duration of treatment, a thorough understanding of the importance of completing the treatment regimen, as prescribed, is paramount, and we can improve our patients' compliance and H. pylori eradication rate by encouraging and assuring patients. However, choosing the treatment should be based on regional patterns of drug susceptibility and resistance and other factors such as a history of recent taking antibiotics (2,11,14,15,(17)(18)(19).…”
mentioning
confidence: 99%